Darstellung und spektroskopische Charakterisierung von Sn2PO4Br - Narda, G. E. (1995)
The synthesis of a new Sn(II) phosphate halogenide, Sn2PO4Br, is described. The com pound was characterized by means of infrared and Raman spectroscopies as well as by its 119Sn-Mößbauer spectrum. The results are compared with those of other Sn2PO4X species.